2022
DOI: 10.1523/eneuro.0234-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Propagation of Seizure Activity in Normal Brain Tissue

Abstract: Epilepsies are characterized by paroxysmal electrophysiological events and seizures, which can propagate across the brain. One of the main unsolved questions in epilepsy is how epileptic activity can invade normal tissue and thus propagate across the brain. To investigate this question, we consider three computational models at the neural network scale to study the underlying dynamics of seizure propagation, understand which specific features play a role, and relate them to clinical or experimental observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This study used whole-brain neuronal network modelling to infer the microscale alterations driving generalised seizure dynamics. Large scale models of epileptic networks have already demonstrated key microscale properties underlying seizures – such as inhibition exhaustion ( Liou et al, 2020 ), excessive inhibitory to inhibitory coupling ( Depannemaecker et al, 2022 ) and hub neurons ( Hadjiabadi et al, 2021 ; Morgan & Soltesz, 2008 ). Here, we studied 3 key parameters – network connectivity, synaptic weights and intrinsic excitability, drawing inspiration from theoretical models of criticality ( Zeraati et al, 2021 ), to relate predictions from criticality theory with observed seizure avalanche dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This study used whole-brain neuronal network modelling to infer the microscale alterations driving generalised seizure dynamics. Large scale models of epileptic networks have already demonstrated key microscale properties underlying seizures – such as inhibition exhaustion ( Liou et al, 2020 ), excessive inhibitory to inhibitory coupling ( Depannemaecker et al, 2022 ) and hub neurons ( Hadjiabadi et al, 2021 ; Morgan & Soltesz, 2008 ). Here, we studied 3 key parameters – network connectivity, synaptic weights and intrinsic excitability, drawing inspiration from theoretical models of criticality ( Zeraati et al, 2021 ), to relate predictions from criticality theory with observed seizure avalanche dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…To model a larger scale, it is necessary to use spiking network models, which represent large populations of neurons and their interactions [74,16,14,75,20,84,97]. Some of these models can be constrained by dynamical properties [62].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Other models make use of the different biophysical properties described for different brain regions, such as the thalomo-cortical loop or the hippocampus [21,22,89,14,80]. Such models are useful to understand the onset [97] and the propagation of seizures in populations of cells [100,74,16]. Spiking network models form the basis for building population models [99,7]; a useful tool to study seizure network properties [73].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…These networks are made up of an excitatory population and an inhibitory population in similar proportions to what is observed in the cortex. These networks are useful for studying complex dynamics associated with the large dimensions of these systems [Carlu et al, 2020, Depannemaecker et al, 2022]. However, having a large number of dimensions can be a limiting factor for the understanding of the representation of its dynamics [Depannemaecker et al, 2023].…”
Section: Introductionmentioning
confidence: 99%